2003
DOI: 10.1093/jac/dkg395
|View full text |Cite
|
Sign up to set email alerts
|

High levels of multiple antibiotic resistance among 938 Haemophilus influenzae type b meningitis isolates from Cuba(1990-2002)

Abstract: In Cuba, the widespread vaccination against Haemophilus influenzae type b prevented a large number of meningitis cases in children caused by strains resistant to multiple antibiotics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 8 publications
2
4
0
Order By: Relevance
“…In the present study the reduction in penicillin resistance was particularly significant among children (Fig. 4), suggesting that vaccination may play a key role in preventing antimicrobial resistance in S. pneumoniae (32), as has been the case for Haemophilus influenzae type b (28).…”
Section: Discussionsupporting
confidence: 62%
“…In the present study the reduction in penicillin resistance was particularly significant among children (Fig. 4), suggesting that vaccination may play a key role in preventing antimicrobial resistance in S. pneumoniae (32), as has been the case for Haemophilus influenzae type b (28).…”
Section: Discussionsupporting
confidence: 62%
“…Our results are in agreement with findings from a previous study conducted in Dakar (10) and in other countries such as Italia (2), Northen Taiwan (14), Cuba (13), and South Africa (5). This suggests that beta-lactamase production could be the major mechanism of antibiotic resistance for these organisms.…”
Section: Discussionsupporting
confidence: 93%
“…The observation that antibiotic resistance is more prevalent in encapsulated isolates, responsible for the majority of meningitis cases, than in nontypeable H. influenzae was also revealed by other authors (4,10,32). The results of some studies showed that there is also an increasing number of H. influenzae isolates resistant to chloramphenicol (e.g., Bangladesh, 21.5%; Paraguay, 20%; Cuba, 44%) and an increasing number of isolates resistant simultaneously to both mentioned antibiotics (2,26,31). Although in our study nonsusceptibility to chloramphenicol was present in less than 2% of the isolates, all of them were simultaneously resistant to ampicillin.…”
Section: Discussionmentioning
confidence: 68%
“…Although we did not find any meningitis BLNAR isolates, the prevalence of such isolates, although rare until recently, is increasing among those responsible for lower respiratory tract infections in Poland, as well as in some other European countries (8). Many countries, such as the United States before the vaccination era and presently Cuba, Bangladesh, and Paraguay, reported a high percentage of ␤-lactamase-producing isolates: 32%, 46.5%, 32.5%, and 30%, respectively (2,26,31,34). In the light of the above data, the percentage of ␤-lactamase producers among Polish meningitis isolates is not very high, although it is three times higher than found among H. influenzae isolates responsible for lower respiratory tract infections in Poland (28).…”
Section: Discussionmentioning
confidence: 99%